The Combination Options and Predictive Biomarkers of PD-1/PD-L1 Inhibitors in Esophageal Cancer - Yang, Hui; Wang, Kunlun; Wang, Tao; Li, Mengxi; Li, Bingxu; Li, Shenglei; Yuan, Ling (Frontiers in Oncology, 2020)
Esophageal cancer (EC) is one of the most common cancers with poor survival in the world. Nowadays, a generous number of clinical trials are underway on the use of immunotherapy in EC patients, especially the programmed death-1/programmed death-ligand 1 (PD-1/PD-L1) inhibitors. However, only a few patients could benefit from single-agent therapy. Others need combination therapies to enhance the response rate and survival. In this review, we focus on PD-1/PD-L1 inhibitors and its combination options in EC patients. We also summarized the potential predictive biomarkers for PD-1/PD-L1 inhibitors treatment.